EVALUATION TECHNIQUES IN PUNJAB, PAKISTAN: EIGHT YEARS OF REFORMS IN HEALTH PROFESSIONAL EDUCATION - Khan, Junaid Sarfraz; Biggs, John SG; Mubbashar, Malik Hussain (Journal of Ayub Medical College Abbottabad, 2011)
Pakistan, the most populated country in the WHO Eastern Mediterranean region has a population of over 170 million, spread over five provinces and four federally administered areas. It has a growth rate of 1.9%. Punjab is the most populous and developed province with an estimated population in 2010 of 81 million. In 2008, Punjab’s development index of 0.60 and a literacy rate of 80% were the highest in the country. In Pakistan, the number of doctors and nurses has risen from 48 to 71 per 100,000 and from 16 to 30 per 100,000, respectively between 1990 and 2003. The major challenge, still, is the imbalance of the population to health-care workers ratio. At the time of creation of Pakistan, King Edward Medical College was the only fully functioning medical college. Over the years, as a result of health reform initiatives, a number of government medical colleges were established in the country. University of Health Sciences, Lahore was established in 2002, having sole jurisdiction over all medical, dental and allied health institutes in the province with the aim of moving medical education towards an outcome-based patient and communityoriented competency-driven system. This paper attempts to clarify how initiatives and reforms in the evaluation process have helped the UHS realise its aims. Evaluation in all branches of higher education has long been taken as a means to an end. The focus of UHS on teacher-training, introduction of behavioural sciences as a compulsory subject and setting up an outcome-based evaluation process, has established a knowledge-acquisition medical education atmosphere. The challenges in the future relate to sustainability through capacity-building and staying abreast with the Best Evidence Medical Education practices worldwide, implementing them to fit our local needs and resources. Keywords: Evaluation, Examination, Education, Punjab, OSCE, OSPE